This preview shows page 1. Sign up to view the full content.
Unformatted text preview: g1 ng N and we deduce that x gN . Therefore Ng gN , and similarly gN Ng . Therefore Ng = gN . Conversely suppose Ng = gN . If x N , then gx = yg for some y N and we see that gxg1 = ygg1 = y N . We deduce that gNg1 N and hence N G , as required....
View
Full
Document
This note was uploaded on 01/02/2012 for the course MATH 3124 taught by Professor Parry during the Fall '08 term at Virginia Tech.
 Fall '08
 PARRY
 Math, Algebra

Click to edit the document details